Moral desicion-making in the criminal justice system : the biasing influence of emotion and intentionality (2019)
It has been shown that gruesome descriptions of harm can increase the punishment given to a transgressor, a biasing effect mediated by negative emotions. However, there is a lack of studies inquiring the influence of such descriptions on moral decision-making in people involved in the criminal justice system. The objective of this study was to explore the influence of gruesome written descriptions on moral decision-making in this group of people. To that end, we recruited attorneys (n=14) and judges (n=28) whose field of specialty was criminal law. In addition, we included a control group of people who did not have a formal education in law (n=28), which did not differ in terms of age to the latter groups. All participants completed a computer based, Spanish-adapted version of a moral decision-making task. A series of text-based stories describing two characters, one inflicting harm on the other, were presented to participants. Transgressor's intentionality (accidental vs. intentional harm) and language used to describe harm (gruesome vs. plain) were manipulated in the stories. Results showed that control subjects rated harmful actions as significantly less morally adequate when harm was described using gruesome language. However, that was not the case of judges and attorneys. This suggests that affective signals can be modulated by the expertise a person has in dealing with emotionally charged, morally relevant scenarios. On the contrary, intentional harmful actions were evaluated as more damaging than accidental harmful actions across all groups, despite the fact that such conditions were equivalent in damage magnitude. Nevertheless, no physiological markers of affective states were found in the electrocardiogram (ECG) recordings associated to the aforementioned phenomena. To our knowledge, this is the first study to demonstrate how expertise can modulate biasing tendencies in moral decision-making processes in the context of the criminal justice system.